An Electronic Control Unit For Erythrocyte Sedimentation Rate Test Device - Sanver, Ufuk; Yavuz, Erdem (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2020)
Erythrocyte sedimentation rate test device, which is expensive as a commercial product, is a commonly used tools in the biomedical field. In this study, a low-cost and effective electronic control unit for erythrocyte sedimentation device was designed and implemented. This microcontroller-based control system manages the circular tray, where blood tubes stay on, for measuring sedimentation level using image processing technique. In order to manage the tray, control unit drives a stepper motor via switching components. Necessary information was transferred to computer via serial port communication in order to display to users. The position of circular tray is sensed for aligning camera and tubes. The measurement number data are taken to microcontroller from RFID Cards using RFID Transceiver. The unit controls also the amount of ambient light in the measurement area. The temperature level of device is measured using temperature sensor and step down by switching on a fan when necessary.